Cellular components and signals required for the cardiac outflow tract assembly in Drosophila. - Zmojdzian, M.; Da Ponte, J.P.; Jagla, K. (Proceedings of the National Academy of Sciences of the United States of America, 2008)
Specification of cardiac primordia and formation of the Drosophila heart tube is highly reminiscent of the early steps of vertebrate heart development. We previously reported that the final morphogenesis of the Drosophila heart involves a group of nonmesodermal cells called heart-anchoring cells and a pair of derived from the pharyngeal mesoderm cardiac outflow muscles. Like the vertebrate cardiac neural crest cells, heart-anchoring cells migrate, interact with the tip of the heart, and participate in shaping the cardiac outflow tract. To better understand this process, we performed an in-depth analysis of how the Drosophila outflow tract is formed. We found that the most anterior cardioblasts that form a central outflow tract component, the funnel-shaped heart tip, do not originate from the cardiac primordium. They are initially associated with the pharyngeal cardiac outflow muscles and join the anterior aorta during outflow tract assembly. The particular morphology of the heart tip is disrupted in embryos in which heart-anchoring cells were ablated, revealing their critical role in outflow tract morphogenesis. We also demonstrate that Slit and Robo are required for directed movements of heart-anchoring cells toward the heart tip and that the cell-cell contact between the heart-anchoring cells and the ladybird-expressing cardioblasts is critically dependent on DE-cadherin Shotgun. Our observations suggest that the similarities between Drosophila and vertebrate cardiogenesis extend beyond the early developmental events.